Penerapan Konsep Maiyyah pada Pondok Pesantren Sidogiri di Kabupaten Pasuruan (Selasar, 2022)
Islamic boarding schools in Sidogiri Pasuruan or abbreviated as PPS, in terms of the number of santri Islamic boarding schools in Sidogiri Currently there are 10,000 students, for the total number of new students in the last 10 years there are 14,560 above which is very increasing, if in the last 10 there are 1,456 santri per year. Based on the results of the data analysis and analysis of the development of the Sidogiri Islamic Boarding School in Pasuruan Regency, the development of main facilities in the form of residential or santri dormitories and supporting facilities is currently needed, so that the development of the Sidogiri Islamic Boarding School is very much needed by applying the concept of Maiyyah (togetherness) infrastructure quality and Islamic in supporting the smooth running of all activities of the santri.